Uso de plantas de cobertura na entressafra de milho e soja - Cremonez, Filipe Eliazar (2018)
An alternative to introduce many different species in this soybean and maize succession system is the cultivation of cover crops in the crop inter-harvest (after corn harvest), without the farmer giving up the main source of income of the enterprise. In this sense, the objective of this work was to make a variety of cover crops after harvesting the maize from the winter and to observe the growth potential and biomass formation of the species, as well as to evaluate the cultures affect of cover crops on the soil and successor crops, mainly the soybean. For that, five species were used: Avena strigosa; Raphanus sativus L.; Vicia sativa L.; Lupinus albus and Sorghum Bicolor cv. Sunchales NR; besides consortium between, R. sativus + A. strigosa; R. sativus + S. Bicolor; V. sativa + A. strigosa; V. sativa + S. Bicolor; L. albus + A. strigosa; L. albus + S. Bicolor; L. albus + V. sativa, totaling 13 treatments. The experiment was carried out in a randomized block design with four blocks (replicates) and each plot was formed by nine sowing rows spaced 0.17 m and 5 meters long. The plants were carried out to 65 days after sowing (DAS), during which time was evaluated, the percentage of soil area covered and incidence of weeds. After 65 DAS, the plants were cutted and the total dry mass, and amount of N, P and K in the plant tissue were evaluated on the day of the plants cut and 20, 40, 60 and 80 days after the cut of the plants. During this last evaluation, it were made assessments of the soil physical properties. Soybean cultivation was also carried out on the straw of the cover crops, from which were evaluated the N, P and K contents in the diagnosis leaf, 100 grain mass and grain yield. For the variables percentage of covered area, quantity and decomposition of dry matter, accumulation and release of P and K, was used an exponential adjustment. For the other variables, the Scott-Knott averages clustering test was used. It was also half-life time was calculated for dry matter and accumulation of N, P and K of the cover plants. For percentage of area covered, it was observed that the culture of R. sativus and A. strigosa were those that developed faster and produced most cover over the soil, thus having a greater suppression effect on weeds. For the formation of dry matter, accumulation and nutrient release, R. sativus and A. strigosa, such as treatments containing these crops, were the most prominent, but with superiority of R. sativus. For the physical properties of the soil, no difference between the treatments was observed for any property evaluated. There, was no difference between the variables evaluated for the soybean crop. In general, thinking about soil cover area, greater weed suppression, greater soil carbon input and greater nutrient cycling, the treatments with R. sativus cultivation are the most recommended for this evaluated period of off-season.